2020
DOI: 10.21203/rs.3.rs-31326/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Test anxiety and emotion regulation among undergraduate medical students in China: the mediating role of psychological resilience

Abstract: Background: Medical students experience a considerable amount of anxiety due to exams. Emotion regulation and psychological resilience are established protective factors of individual mental health, however, the investigations for the effects of anxiety were limited. The goal of the present study was to examine the relationship of psychological resilience and emotion regulation with test anxiety and the associated factors of them among medical students. Methods: In this cross-sectional survey, a simple random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Moreover, remote online exams were launched as an assessment approach to investigate students' academic performance during the current situation. Many studies have been done to determine the anxitey level of students, especially medical students, during exams up to now and most of these studies, from all over the world, indicated a high levels of this phenomenon in medical students (10). Some studies measured the test anxiety level too high, which performing serious interventions were considered necessary (10,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, remote online exams were launched as an assessment approach to investigate students' academic performance during the current situation. Many studies have been done to determine the anxitey level of students, especially medical students, during exams up to now and most of these studies, from all over the world, indicated a high levels of this phenomenon in medical students (10). Some studies measured the test anxiety level too high, which performing serious interventions were considered necessary (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been done to determine the anxitey level of students, especially medical students, during exams up to now and most of these studies, from all over the world, indicated a high levels of this phenomenon in medical students (10). Some studies measured the test anxiety level too high, which performing serious interventions were considered necessary (10,11). However, by the expansion of COVID-19, the learning and evaluation of the medical students shifted to be online more than before.…”
Section: Introductionmentioning
confidence: 99%
“…This has been confirmed in previous studies with secondary school students (Akbari et al, 2014;Jamshidi et al, 2018). In the same vein, Liu et al (2020) confirmed that psychological resilience and emotion regulation can predict emerging test anxiety. In contrast to these studies, Sakka et al (2020) denied the correlation between test anxiety and resilience among secondary school students.…”
Section: Discussionmentioning
confidence: 65%
“…Resilience in the academic context has been the subject study of many researchers, who approached the issue within its relationship to test anxiety, and as an anxiety predictive mediator variable, both for university students (Gaber & Ali, 2016;Hayat et al, 2021;Hye Sook & Ya Ki, 2014;Liu et al, 2020), and among secondary school students (Akbari et al, 2014;Jamshidi et al, 2018). In this regard, the study carried out by De La Fuente et al (2017) considers that high levels of self-regulation create a high level of resilience among university students, as it is a potential mediating variable to face pressure and stress.…”
mentioning
confidence: 99%
See 1 more Smart Citation